Hepatocellular carcinoma and multidrug resistance: Past, present and new challenges for therapy improvement - Cuestas, María Luján (2015)
Hepatocellular carcinoma (HCC) is the most common malignancy of the liver and the third cause of cancer death worldwide. Chronic hepatitis due to HBV and HCV infection are two major risk factors for HCC worldwide. Advances in early detection and treatment have improved life expectancy of patients with HCC. However, this disorder remains as a disease with poor prognosis. In fact, epidemiological studies have shown that the median survival of patients is 8 months and approximately 20% of them survive one year, while only 5% remain alive after three years. Additionally, HCC is particularly difficult to treat because of its high recurrence rate, and its resistance to conventional chemotherapy due to, among other mechanisms, the over-expression of several members of the ATP-Binding Cassette (ABC) protein family involved in drugs transport. Fortunately, there is evidence that these patients may benefit from alternative molecular-targeted therapies. This manuscript reviews the current knowledges on the etiology, molecular mechanisms involved in HCC development and the current therapy strategies for the management of this malignancy. The challenges in the development of drug delivery systems for the targeting of antitumoral drugs to the liver parenchyma are also discussed. Finally, perspectives in the design of a more efficient pharmacotherapy to overcome multidrug resistance are reviewed.